Efektivitas Pelaksanaan Diversi Bagi Anak Yang Berhadapan Dengan Hukum di Pengadilan Negeri Kelas IA Jambi - Triamy Rostarum; Dedy Syaputra; Ahmad Dani (Legalitas: Jurnal Hukum, 2026)
Diversion in the juvenile criminal justice system is an obligation that must be pursued at every stage of the legal process, starting from investigations by the police, prosecution by the prosecutor's office, to examinations in court as mandated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The purpose of this study is to determine and analyze the implementation of diversion for children in conflict with the law at the Class IA Jambi District Court and to identify and analyze factors that support and hinder the effectiveness of the implementation of diversion at the court level at the Class IA Jambi District Court. The method used in this study is the empirical juridical research method. Data collection in this study was carried out through interviews and document reviews. From the results of this study, it can be concluded that the implementation of diversion at the Class IA Jambi District Court has been carried out in accordance with the principles of restorative justice as mandated by Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. In general, the implementation of diversion at the Class IA Jambi District Court has been effective, marked by the successful resolution of several cases through peaceful agreements, including apologies, commitments not to repeat the offense, and acceptance from the victim. Supporting factors include the availability of a strong legal basis, active participation of the victim's and perpetrator's families, commitment from judges and court officials, an appropriate and sensitive approach to children, and the perpetrator's good intentions to correct mistakes. Factors hindering the implementation of diversion include crimes that carry a sentence of more than 7 years, repeat offenses, perpetrators not meeting the age requirements stipulated in the Child Protection Act (UU SPPA), and the failure to reach an agreement between the parties.